Development of Figma Educational Game Based on Mathematics Computational Thinking Ability for Vocational Students - Fauziyah, Nida’; Rosdiana, Ratna; Maharani, Anggita; Hapsari, Trusti (SAINTIS Publishing, 2024)
Developing educational games using Figma can help educators create engaging and interactive learning media. This also applies at the vocational school level to improve learning outcomes, especially in mathematics, which students rarely favor because it is considered a complex subject. The main problem faced by vocational students related to employability still needs to be considered higher, which is caused by the lack of availability of interactive media to hone the skills desired by the work industry, including soft skills such as logical thinking and technical functions such as computational thinking. This research aims to create an educational game based on mathematical computational skills in vocational students through a Research and Development (RD) approach by applying 4 of the five stages of the ADDIE Method, namely Analysis, Design, Development, Implementation, and Evaluation. From the four stages of the ADDIE Model, an Educational Game design using Figma entitled